Zooming into the first year after parental death: Loss and recovery in adult mental health - Kateryna Sytkina (Elsevier, 2024)
The initial year after parental death is a critical period for grief and coping. Despite its significance for declines in and recovery of adult mental health, this initial period is not sufficiently captured in existing research following changes across annual or even broader intervals. This paper assesses the impact of the first and second parent's death on adult mental health on more fine-grained monthly timescales. Using data from up to 12 waves of the German Socio-Economic Panel Study (GSOEP) and fixed-effects models with yearly and monthly impact functions, the analysis yielded two main findings. First, mental health declines were much deeper when measured on a monthly scale. The magnitude of drops recorded within the first two months following parental death approximately doubled those measured at an annual scale. Second, recovery occurred much faster when recorded on a monthly timescale and was evident already a few months after the loss of a parent. Overall, this study suggests that reaction and adaptation to parental death are stronger and faster than previously documented. The study additionally identified variations in mental health responses. Those who lost their first parent had worse mental health a year after the event compared to those who lost their second parent. The most significant decline in mental health, around 10 points, occurred among daughters one to two months after their mother's death. When the mother died first, the impact was more severe on mental health, especially among younger daughters and sons.